THE USE OF SMARTPHONE AND STUDENTS' LEARNING STRATEGIES IN LEARNING ENGLISH - Nurhaeni, - (2016)
The purpose of this research was to investigate whether or not the smartphone use influence students' learning strategies. The students of Islamic Economy Department that currently enrolled in English class were taken as the sample of this research. Correlational study was applied with further regression analysis conducted on the collected data. The instruments used in this research were questionnaires and interview. The findings revealed that the use of smartphone influence students' learning strategies. Furthermore, cognitive and social/affective strategies are the strategies that were influenced the most and metacognitive strategies were influenced the least by the use of smartphone in learning English. The cognitive and social/affective were influenced the most since the students mostly use smartphone in learning English for specific task or direct answers, and also use smartphone to post or chat in English using social media. Keywords: Smartphone use, learning strategies